2016
DOI: 10.1016/j.jmgm.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Homology modeling of a Class A GPCR in the inactive conformation: A quantitative analysis of the correlation between model/template sequence identity and model accuracy

Abstract: With the present work we quantitatively studied the modellability of the inactive state of Class A G protein-coupled receptors (GPCRs). Specifically, we constructed models of one of the Class A GPCRs for which structures solved in the inactive state are available, namely the β2 AR, using as templates each of the other class members for which structures solved in the inactive state are also available. Our results showed a detectable linear correlation between model accuracy and model/template sequence identity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 46 publications
(45 reference statements)
0
29
0
Order By: Relevance
“…Using the GPCR-SSFE 2.0 modeling server ( Worth et al, 2017 ), we found the inactive-state structure of the lyso-phospholipid sphingosine 1-phosphate receptor [S1PR1, PDB entry 3V2Y ( Hanson et al, 2012 )] with a sequence similarity in the transmembrane region of 56% and a sequence identity to hMC4R of 30% (Blossum62 matrix, Supplementary Figure S1 ). Such high sequence similarity between the suggested template and MC4R is important for the accuracy of the structural model ( Costanzi et al, 2016 ). The template structure is characterized by a leucine at position 5.50 in TM5 ( Ballesteros and Weinstein, 1995 ) and in consequence shows a regular α-helical conformation, as also expected for hMC4R.…”
Section: Methodsmentioning
confidence: 99%
“…Using the GPCR-SSFE 2.0 modeling server ( Worth et al, 2017 ), we found the inactive-state structure of the lyso-phospholipid sphingosine 1-phosphate receptor [S1PR1, PDB entry 3V2Y ( Hanson et al, 2012 )] with a sequence similarity in the transmembrane region of 56% and a sequence identity to hMC4R of 30% (Blossum62 matrix, Supplementary Figure S1 ). Such high sequence similarity between the suggested template and MC4R is important for the accuracy of the structural model ( Costanzi et al, 2016 ). The template structure is characterized by a leucine at position 5.50 in TM5 ( Ballesteros and Weinstein, 1995 ) and in consequence shows a regular α-helical conformation, as also expected for hMC4R.…”
Section: Methodsmentioning
confidence: 99%
“…34,35 An initial automatic sequence alignment was first obtained with the Blosum 62 matrix, with penalties for the opening and the extension of gaps set to 4 and 3, respectively. This initial alignment was then inspected and manually adjusted, if needed, to ensure the matching of the motifs that identify each of the seven TMs and the absence of internal gaps within the boundaries of the membrane-spanning domains.…”
Section: Methodsmentioning
confidence: 99%
“…34 Differences in sequence length between the two aligned receptors were accounted for by placing gaps in the loop domains, following our recently described procedures for the alignment of domains that have fewer residues in the modeled receptor than in the template ( deletions in the modeled receptor ) and for the alignment of domains that have more residues in the modeled receptor than in the template ( insertions in the modeled receptor ). 35 Finally, as a number of residues in the N-terminus, C-terminus and third intracellular loop (IL3) of the D 2 receptor are not solved in the crystal structure, we expunged from the sequence alignment the residues of the α 1B -adrenoceptor that extend beyond those crystallographically solved for the template. The resulting alignment is shown in Figure 5.…”
Section: Methodsmentioning
confidence: 99%
“…We did so using class-A GPCR comparative modelling, a well-known bioinformatics strategy aimed at gathering novel structural information on this receptor family that indeed encompasses about 70% of all drug-targets [48,49]. Although GPR17 experimental structure has not been solved yet, the availability of homologous proteins to be used as templates, combined with specific class-A GPCR modelling techniques [50,51], allowed us to obtain an accurate and validated model, with a well-shaped binding site, useful for the subsequent HTS procedures [29,31,36,52,53]. Accordingly, in the very last years, homology modelling has been successfully applied also by other groups for identifying both similar and chemically diverse GPR17 ligands [23,54].…”
Section: Plos Onementioning
confidence: 99%